HUBUNGAN PENGGUNAAN MEDIA SOSIAL INSTAGRAM @sekolahvokasiipb DENGAN PEMENUHAN INFORMASI AKADEMIK MAHASISWA KOMUNIKASI DIGITAL DAN MEDIA - Alvito Haris; Wahyu Budi Priatna; Rici Tri Harpin Pranata; Sutisna Riyanto (Jurnal Sarjana Ilmu Komunikasi (J-SIKOM), 2026)
This study examines the relationship between the use of the Instagram account @sekolahvokasiipb and the fulfillment of academic information needs among students of the Digital Communication and Media Study Program. The study is grounded in the Uses and Gratifications Theory, which positions students as active audiences who deliberately select media to satisfy their informational needs, and the Circular Model of SOME, which emphasizes content sharing, optimization, management, and audience engagement in digital communication. A quantitative approach was employed by distributing Likert-scale questionnaires to 84 students who follow the @sekolahvokasiipb Instagram account. Due to non-normal data distribution, the Spearman correlation test was applied. The results indicate that both Instagram usage and the fulfillment of academic information needs are categorized as high to very high. The correlation analysis reveals a very strong and significant relationship between the two variables (r = 0.830; p < 0.001). These findings demonstrate that Instagram functions effectively as a channel for digital academic communication by providing accessible, relevant, and timely information. This study contributes to digital academic communication research by empirically integrating the Uses and Gratifications Theory with the Circular Model of SOME in explaining social media engagement within higher education institutions. Keywords : Uses and Gratifications, Circular Model of SOME, Digital Academic Communication, Instagram